2017
DOI: 10.1039/c7ra03056h
|View full text |Cite
|
Sign up to set email alerts
|

The removal of heavy metal ions from aqueous solutions by amine functionalized cellulose pretreated with microwave-H2O2

Abstract: Microcrystalline cellulose pretreated with microwave-H2O2 was introduced with carboxyl and amino groups to obtain a new promising bioadsorbent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(32 citation statements)
references
References 27 publications
2
30
0
Order By: Relevance
“…Cellulose powder has hydroxyl groups on the surface and is therefore easily dispersible in polar solvents such as water [33][34][35][36]. Another form of cellulose specifically used for the synthesis of composites is microcrystalline cellulose [37,38], which has similar characteristics to cellulose powder, but has a larger exposed surface area, thus increasing its reactivity in the chemical environment and facilitating interaction with the other components of the mixture. For the same reason, nanocellulose has also been used for the synthesis of cellulose-based composites [39,40].…”
Section: Cellulose-pei Composites: Synthetic Strategies 21 Cellulosmentioning
confidence: 99%
See 1 more Smart Citation
“…Cellulose powder has hydroxyl groups on the surface and is therefore easily dispersible in polar solvents such as water [33][34][35][36]. Another form of cellulose specifically used for the synthesis of composites is microcrystalline cellulose [37,38], which has similar characteristics to cellulose powder, but has a larger exposed surface area, thus increasing its reactivity in the chemical environment and facilitating interaction with the other components of the mixture. For the same reason, nanocellulose has also been used for the synthesis of cellulose-based composites [39,40].…”
Section: Cellulose-pei Composites: Synthetic Strategies 21 Cellulosmentioning
confidence: 99%
“…The use of GAL involves cross-linking between (b)PEI and cellulose through the formation of a Schiff base and a hemiacetal, as shown in Scheme 3. The reaction can be conducted one pot through simple stirring in polar solvents [35,38], and it is possible to operate even at room temperature. However, by increasing the reaction temperature, it is possible to increase the value of the cellulose/PEI ratio, obtaining a more stable product thanks to the higher amount of the cellulosic polymer [33].…”
Section: Cross-linking Strategiesmentioning
confidence: 99%
“…It was found that the adsorption efficacy of Cd(II) increased with increasing pH of the solution, and reached the maximum adsorption value at pH (6-7). Zhu et al [36] showed similar results for their research work on the adsorption of Cd(II) and Pb(II) ions via amine-functionalized cellulose. The low metal sorption at lower pH, may be explained on the basis of active sites being protonated, resulting in a competition between H + and M 2+ for occupancy of the binding sites [37].…”
Section: Effect Of Phmentioning
confidence: 58%
“…The experimental and calculated values of q e are also very close, as shown in Table 1; thereby, the pseudo-second-order kinetic equation is more appropriate for describing the adsorption kinetics behaviors of Cd(II) on the 1,2,3,4-tetrahydropyrimidine derivative (4). Zhu and colleagues [36] showed that the pseudo-second-order equation better depicts the sorption kinetics of Pb(II) and Cd(II) on amine-functionalized cellulose.…”
Section: Kinetic Studymentioning
confidence: 61%
“…In addition, an increasing trend in the bands 2917 and 2846 cm −1 was observed in the following order: uncrosslinked CNF < with crosslinker (unheated) < with crosslinker (heated). These two bands correspond to the aliphatic C–H stretching 34 . The increase in this peak in the unheated sample (compared to CNF without crosslinker sample) is believed to result from the presence of the crosslinker which contains multiple aliphatic C–H bonds on its backbone.…”
Section: Resultsmentioning
confidence: 99%